Leadership Dynamics and Employee Voice in Improving Employee Performance - Kasno Kasno; Ulil Hartono; Rega Ababil (Cakrawala Repositori IMWI)
This study aimed to analyze the influence of leadership, employee voice behavior, and emotional exhaustion on employee performance at KSP Teratai Mas Lumajang. Employee performance is a crucial factor in achieving organizational goals, particularly in cooperative institutions that rely heavily on the quality of human resources in delivering services to members. Issues related to leadership, low employee participation in expressing ideas, and emotional exhaustion were considered to affect employee performance. This study used a quantitative approach with multiple linear regression analysis. Data were obtained by distributing questionnaires to all employees of KSP Teratai Mas Lumajang. A saturated sampling technique was used, involving 48 respondents. Data analysis was conducted to determine the influence of independent variables on employee performance, both partially and simultaneously. The results showed that leadership had a positive and significant effect on employee performance. Employee voice behavior also had a positive and significant effect on employee performance, indicating that employees who actively expressed ideas and suggestions could improve organizational performance. Meanwhile, emotional exhaustion had a negative and significant effect on employee performance, meaning that higher levels of emotional exhaustion were associated with lower employee performance.